USING NURSERY RHYMES TO TEACH VOCABULARY: A CASE STUDY OF FIFTH-GRADE STUDENTS IN A PUBLIC ELEMENTARY SCHOOL IN BANTEN - Hidayatillah, Nur Salamah; Wijayanti, Murti Ayu; Utomo, Dhafid Wahyu (Universitas Jambi, 2025)
The study aims to determine the learning process, the challenge, and student responses on teaching vocabulary by using nursery rhymes in SDN Tembakang 2. The method used in this research is qualitative. The data was collected through observation, interview, and documentation. The participants of this research are the fifth-grade student which consist of 20 students and the teacher. Based on the findings, the researchers found that the teacher faced difficulty in finding appropriate nursery rhymes with the material, and most of the students faced difficulty in self-confidence. However, the students positively responded to the implementation of nursery rhymes in teaching vocabulary, the students can pronounce and remember the vocabulary easily after singing nursery rhymes. Their English score also increased in themes 1,2, and 4 which the teacher used nursery rhymes as teaching media. In conclusion, the use of nursery rhymes as teaching media helps students at the elementary level in learning the vocabulary.